Manipulating Charge Dynamics in Carbon Nitride by Carbon Dot Doping for Efficient Photocatalysis - Lingfeng Ouyang; Maggie Ng; Zhang‐Hong Zhou; Hao Wu; Man‐Chung Tang; Season Si Chen (Advanced Science, 2025)
Abstract Graphitic carbon nitride (g‐C3N4), a prominent metal‐free semiconductor photocatalyst, faces limitations due to its high exciton binding energy. While significant efforts have been focused on optimizing charge‐carrier processes, the interplay of exciton and free carrier in this system have received less attention. Herein, this density‐functional theory (DFT) and time‐dependent DFT calculations demonstrate that carbon dot‐functionalized g‐C3N4 (g‐C3N4/CD), synthesized via a facile thermal polymerization, shifts the excited state from localized to charge transfer characteristics. The g‐C3N4/CD exhibits reduced exciton binding energy from 41.0 to 24.6 meV, as shown by temperature‐dependent photoluminescence spectroscopy. Particularly, g‐C3N4/CD‐10 (10 wt.% CD solution in precursors) achieves a 3‐fold increase in the photodegradation rate (k = 0.020 min⁻¹) of an emerging environmental pollutant, levofloxacin (LEV), under 10 W LED light. Enhanced photocatalytic performances correlate with optimized band structure and efficient charge transport, as confirmed by photophysical and photoelectrochemical analyses. Although the excited state lifetime in g‐C3N4/CD is slightly reduced compared to pristine g‐C3N4, photocatalytic activity remains unaffected, underscoring the critical role of charge excited state in enhancing photocatalytic efficiency. This work offers insights onto the potential of manipulating charge transfer excited state dynamics for improved g‐C3N4‐based photocatalysis in environmental applications.